El cierre de las escuelas comunitarias y su incidencia en el proceso educativo. Análisis de caso en la comunidad Chitachaka, parroquia Juan Montalvo, cantón Cayambe - Pujota Conlago, Segundo Vicente (2018)
This research provides us with a wide knowledge about the reality of the Jefferson Mecham School, through the information provided by the direct actors, teachers, parents and inhabitants of the Chitachaka community, about the problems that arose after the closure of the school community school. From the results of this research it is possible to understand the reality of the dynamics of this particular community, where the children's joy / as it is no longer the same, previously studied in its own cultural and social context now alien to its environment. In the first part of the work the historical overview of the community and the school is presented, in the second part the most relevant points of the education law, political, socio-economic and administrative causes are exposed. The third part presents a brief analysis of the impact caused, in the community environment, the closure of the school, a comparative analysis of the law and its results in the field and on all the actors involved. In the methodological field, the present research works with the inductive method and a descriptive and explanatory inquiry is carried out. The specialized instruments for data collection, dedicated services, parents, children and teachers. The data collected was processed qualitatively and from its analysis it was possible to draw up some conclusions and recommendations.